EFFECT EXTRACT FRUIT PALA (NUTMEG) AS AN ALTERNATIVE PRESERVATION FOR QUALITY OF CAKALANG FUFU FISH - Fahmi Abdul Hamid (Poltekkes Kemenkes Semarang, 2020)
Nutmeg flesh becomes limba during the harvest season. To increase the benefits and economic value, nutmeg which is antibacterial in nature can be processed and developed into alternative preservatives. The purpose of this study was to determine the effect of nutmeg extract as an alternative employee to the quality of fufu cakalang fish (smoked cakalang fish). This type of quantitative research is a randomized block design. The total sample is 9 units, consisting of 3 treatments and 3 blocks, with a simple random sampling technique.test E Coli with SNI method and organoleptic test with score method. Data were analyzed with the help of a computer. Fufu cakalang fish scores were organoleptically 1000 grams of nutmeg extract and 500 grams were 8 and the control group score was 7. The average growth of E Coli in the control group was 4.6667 ± 2.08167 and the treatment of 500 grams of the average contamination or growth of microbes E Coli. 0.6667 ± 1,15470.growth E Coli occurred on the sixth day and increased on the ninth day of storage. One way ANOVA statistical test, between the treatment groups of 1000 grams, 500 grams and the control group showed that there were differences in the growth of microbiology E coli with a calculated F value of 10.118 significant at p 0.012 less than 0.05. It was concluded that the administration of nutmeg extract can provide differences in the growth of E Coli.